Unravelling the Antiproliferative Activity of 1,2,5-oxadiazole Derivatives - EHRSAM, DANIEL; PORTA, FABIOLA; MORI, MATTEO; SCHWABEDISSEN, HENRIETTE E. MEYER ZU; DALLA VIA, LISA; GARCIA-ARGAEZ, AÌDA NELLY; BASILE, LIVIA; MENEGHETTI, FIORELLA; VILLA, STEFANIA; GELAIN, ARIANNA (Anticancer research, 2019)
To develop several new derivatives aimed to complete the studies concerning the antiproliferative profile of the oxadiazole derivative MD77. The substitution pattern around the phenyl rings of this compound was analyzed through the synthesis of positional isomers and of analogues bearing different substituents at the para positions ( ). The results of the antiproliferative activity of these derivatives versus HCT-116 and HeLa cancer cell lines shed light on the effects of the presence, nature and position of such substituents. Notably, derivative , a regioisomer of in which the substituents at the para positions of the phenyl rings were inverted, showed the best antiproliferative profile, exhibiting a significant activity also against MCF7 and MDA-MB 468 cancer cell lines. Preliminary results showed the ability of compound to reduce the viability of cancer cells by counteracting human recombinant topoisomerase II α relaxation activity.